Industrialization and Environmental Issues in China - Geng, Wang; Wei, Li; Guang, Tian; Guang, Tian (Journal of Management Policy and Practice, 2017)
Serious environmental obstructions have occurred due to the weak basis and arbitrary industrial structures in contemporary China. The layout of industrial structure has direct impacts on the outcome of the industrialization, and the benefits for the local people could be crucial factors during the process of industrial development. It discusses the major causes for the environmental disasters, investigates and analyzes the factors that generate environmental problems based on field study materials. It proposes the workable solutions to balance the development between industrial construction and environmental protection.